Bicycle helmet law does not deter cyclists in Finland. (October 2018) - Radun, Igor; Olivier, Jake
Highlights: Bicycle helmets are effective in reducing head and face injury in a crash. There is a concern helmet laws might deter cycling. Cycling has declined in Finland from the late 1990s to early 2010s. Immediately after law, helmet use was not an important reason for not cycling. It is unlikely repealing the Finnish bicycle helmet law will increase cycling. Abstract: Bicycle helmet legislation (BHL) in Finland went into effect in January 2003 and applies to cyclists of all ages. There are no mechanisms to fine cyclists riding without a helmet; however, helmet wearing rates are 64% in Helsinki and 42% across Finland. Our aim was to discuss possible effects of BHL on cycling in Finland. We used data from the 1998/1999, 2004/2005 and 2010/2011 Finnish National Travel Surveys. Data across three surveys suggest cycling has declined from before to after BHL. In a 2004/2005 survey, however, only 0.063% (95% CI: 0.02–0.10%) of responders identified helmet use as their most important obstacle to cycling. It is unlikely BHL is a causal factor in the downward trend in Finnish cycling. Lack of cycling infrastructure and concerns for safety are much more common reasons given.